Vitamin E diary dietary intake in premenopausal healthy women and its relationship with the recommended diary dietary intake - Luis Manuel Puerto-Parejo; Olga Leal-Hernández; Ignacio Aliaga; Raúl Roncero-Martín (Colegio de Enfermería de Caceres, 2017)
Background: The health benefits arising from the antioxidant vitamin E is well recognized and itsrecommended dietary intake for the general population have been established. However, there is still aneed for assessing antioxidant vitamin intake in different population groups. Objective: To assess intake ofantioxidant vitamin E and to identify its major sources in the diets of healthy premenopausal women from Extremadura. Material and methods: The study group consisted of 123 premenopausal women from Spanish population. Antioxidant vitamin dietary intake was assessed by individual 7-day records. Data wasanalyzed using updated "Spanish Food Composition Tables". Results: The average daily intake ofantioxidant vitamin E was: 2.58±0.85 mg/day. Dietary vitamin E was around 76.54% lower than thatrecommended. Diets that were deficient in vitamin E were recorded in the 100% of the interviewedpremenopausal women from Extremadura. Conclusions: The average intake of antioxidant vitamin E wasnot found to be in recommended range, no significant differences were observed between the lowest andthe highest intake. They were no differences in the consumption of food products recognized as majorsources of vitamin E in the study population. It is therefore necessary to increase the consumption of foodsthat provide a valuable dietary source for this vitamin.